Treatment of Cervical Chlamydial Infection With Amoxicillin/Clavulanate Potassium - Melinda S. Mann; Sebastian Faro; Maurizio L. Maccato; Raymond H. Kaufman (Hindawi Limited, 1993)
Objective: To determine if amoxicillin/clavulanate potassium is effective in the treatment of Chlamydia trachomatis endocervicitis.